Penerapan Model Teams Games Tournament (Tgt) Berbantuan Media Baamboozle Untuk Meningkatkan Minat Belajar Siswa Pada Materi Pewarisan Sifat di Kelas IX SMP - Rahma Hanifa Izzaturrahman; Nurwanti Fatnah; ahmadi, Adiyanti (LPPM Institut Pendidikan Nusantara Global, 2025)
Learning interest is a crucial factor that determines student engagement in the learning process, especially in science subjects that involve abstract concepts such as heredity. This study aims to improve the learning interest of ninth-grade junior high school students through the application of the cooperative learning model Teams Games Tournament (TGT) integrated with the interactive media Baamboozle. This research is a Classroom Action Research conducted in two cycles. The subjects were 30 students from grade IX of SMP Negeri 2 Sumber. Data collection techniques included questionnaires, observation, interviews, and documentation. The results showed that the implementation of the TGT model assisted by Baamboozle significantly increased students’ learning interest, as indicated by the increase in the average learning interest score from 64.43% (pre-cycle) to 86.43% (cycle II). These findings were supported by observation, documentation, and interview data that revealed improved student engagement, attention, and enthusiasm throughout the learning process. Therefore, the TGT model assisted by Baamboozle is effective in creating a fun, competitive, and collaborative learning environment in science education. This study contributes theoretically to the development of science learning models that integrate digital media with cooperative strategies, and practically offers an innovative instructional approach that aligns with the characteristics of 21st-century learners and supports student-centered learning in the context of the Merdeka Curriculum.